Experimental Study on Coal Gasification in a Full-Scale Two-Stage Entrained-Flow Gasifier - Guangyu Li; Luping Wang; Chaowei Wang; Chang’an Wang; Ping Wu; Defu Che (Energies, 2020)
In this paper, coal gasification characteristics in the reductor were investigated in a full-scale two-stage pressurized entrained-flow gasifier, which has been seldom conducted previously. The present study aimed at elucidating the effects of gasifying agent concentration, coal input rate, and operation period under full reductor load on the performance of a utility two-stage pressurized entrained-flow gasifier for the first time. When the steam input in the combustor was raised from 3318 kg/h to 5722 kg/h, the total outputs of H2, CO, and CO2 were increased by 1765 Nm3/h and 2063 Nm3/h, respectively, while the CH4 output was decreased by 49 Nm3/h. The coal conversion rate was minimal at low steam input. In addition, more coal gasified in the reductor could increase the output of CH4, while CH4 could reach 1.24% with the coal input in the range of 8000–10,000 kg/h. The present work can offer a further understanding of the gasification performance in the reductor of the full-scale two-stage pressurized entrained-flow gasifier, and motivates the potential for clean utilization of coal resource.